Handbook of plastics, elastomers, and composites - Harper, Charles A (McGraw-Hill, 1992)
Aiming to provide a broad range of new industrial techniques and developments, this book presents the latest information, data and guidelines. It also categorizes plastics and elastics, identifies the materials in each category and presents the advantages of each for major products.